2018
DOI: 10.5935/0004-2749.20180081
|View full text |Cite
|
Sign up to set email alerts
|

Oral omega 3 in different proportions of EPA, DHA, and antioxidants as adjuvant in treatment of keratoconjunctivitis sicca in dogs

Abstract: Oral treatment with ω-3 containing a higher proportion of EPA than DHA increased the effectiveness of topical tacrolimus 0.03% in the treatment of keratoconjunctivitis sicca in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Previously, the deficiency of DHA and EPA was found to correlate with the clinical manifestations of DES [21]. Consistently, the daily supplementation of these ω-3 PUFAs was found to reduce or reverse the symptoms of DES in different species including humans [74][75][76]. DHA is a well-recognized precursor of proresolving lipid mediators, controlling epithelial wound healing, inflammatory cell migration and nerve regeneration [21].…”
Section: Discussionmentioning
confidence: 80%
“…Previously, the deficiency of DHA and EPA was found to correlate with the clinical manifestations of DES [21]. Consistently, the daily supplementation of these ω-3 PUFAs was found to reduce or reverse the symptoms of DES in different species including humans [74][75][76]. DHA is a well-recognized precursor of proresolving lipid mediators, controlling epithelial wound healing, inflammatory cell migration and nerve regeneration [21].…”
Section: Discussionmentioning
confidence: 80%
“…Twenty studies were performed in canine patients (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and three studies in feline patients (32)(33)(34), with a total of 978 dogs and 68 cats evaluated. In dogs, five types of nonneoplastic diseases were studied: i) allergic dermatitis (13,16,17,(27)(28)(29)(30)(31), ii) osteoarthritis (12,(19)(20)(21)(22)26), iii) periodontal disease (14), iv) keratoconjunctivitis sicca (24) and v) cardiovascular disorders (18,23). According to the eligibility criteria, an additional study was reviewed for assessing a health issue, such as a poor quality haircoat, rather than a particular disease (25).…”
Section: Resultsmentioning
confidence: 99%
“…The methods most often used in the investigator's assessment were: i) scoring systems and ii) scales (12-14, 16, 17, 20-23, 25-29, 34). In addition, patients' status was assessed through i) subjective clinical evaluation (12,33), ii) objective clinical tests and measurements (18,24), iii) medication adjustment needs (21), iv) visual analogue scale (VAS) (17,26,34), v) force plate analysis (19,20), vi) activity monitor (AM) counts (34) and vii) time periods, such as disease-free interval (DFI) (15) and survival time (ST) (15,23). Regarding the owners' evaluation, questionnaires were carried out to obtain information on the severity of clinical signs (13, 17, 19-22, 27, 34), their overall opinion on the treatment response (12,13,30,31) and quality of life (34), as well as their perception of the clinical condition (29), behavior (32) and activity of their pets (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, differences in their influence on transduction pathways, the release of inflammatory cytokines, and the expression of genes involved in lipid metabolism have also been reported [ 40 ]. In the field of ophthalmology, one article compared the effect of two different EPA/DHA formulations (1/4.5 and 1.5/1) as adjuvants to topical tacrolimus in a model of keratoconjunctivitis sicca (dry eye disease) in dogs [ 41 ]. Authors reported better clinical and biochemical outcomes after supplementation with the oral formulation containing a higher proportion of EPA.…”
Section: Discussionmentioning
confidence: 99%